Divisional performance measurement in the retail financial service sector: An empirical study. Issue 2 (13th February 2017) - Agyei-Mensah, Ben Kwame
Abstract : Purpose: Focussing on responsibility theory of management accounting, the purpose of this paper is to test how performance measurements are applied in divisionalised financial service companies. Management accounting theory suggests that two different measures of branch performance should be computed: one to evaluate the economic performance of each branch and the other to evaluate the performance of branch managers (managerial performance). It also advocates that the evaluation of a manager's performance should consist of only those factors under his or her control. That is, divisionalised performance measurement should be based on the application of the controllability principle, the study also identified the contingent factors that impinged on the selection of performance measures and the allocation of common costs (ACCs) to branches. Design/methodology/approach: Using a survey questionnaire and analysis of financial statements of the 129 respondent companies the application of financial performance measures: non-financial performance measures and ACCs were tested. For the purpose of this study, dummy variables were assigned to represent whether or not an item is used, if an item is used 1 is assigned to that item and 0 if an item is not used. The values assigned were then summed up to represent the total score for each company. Descriptive statistics and regression analysis was performed to test the six hypotheses of the study. Findings: The study found that a substantial majority of respondents used different performance measures to evaluate the performance of their branch managers and the economic performance of branches. Both financial and non-financial performance measures were equally used in measuring the performance of branches and branch managers. The study also found that branch managers do not have full autonomy and control over the allocation of common resources costs which form part of their evaluation, even though accounting theory suggest that. The regression analysis results showed that firm size, liquidity and leverage were the factors that influence the decision to employ financial performance measures, non-financial performance measures and ACC by the respondent companies. Research limitations/implications: Despite the popularity of the balanced scorecard it is surprising to note that none of the respondents have ever used this as a performance measure. The implication is that knowledge of this performance measure is very low among the respondents. The excessive use of uncontrollable factors in the measurement process can reduce the morale of the staff involve hence steps should be taken to reduce their use. Originality/value: This is one of the few studies conducted on the application of performance measures in the financial services and also in a developing country setting. The findings would help organisations in both developing and developed economies to improve upon the application of performance measurement techniques in their branches/divisions.